Uma política de identificação de fundos, descrição e difusão em Instituições Federais de Ensino Superior (IFES) - Cé, Graziella (2016)
The Federal University of Health Sciences of Porto Alegre (UFCSPA) has its origins in the year of 1953, being a university specialized in the health area, built in a historical and cultural moment of shortage of doctors in the state of Rio Grande do Sul. This institution possesses extension, research and teaching function. Its historical construction, as well as the historical value of its collection under custody justifies the need of this research, since that, over the years, the university passed through several structural, juridical and regulatory changes. The objective of this research is the identification and the proposition of a systematic arrangement and description aiming the diffusion of the research instruments: guide and inventory, through the use of the digital platform, ICA-Atom (AtoM). The documents of this collection, prove the political, social and cultural relations of this institution, since its foundation until the curricular transformation and the creation of academic courses. As a theory to support the research, references related to culture, cultural heritage and archival documentary heritage were discussed. The aspects relative to Post Modern Archival, Contemporary Diplomatic and archival document have also been discussed. Lastly the archival functions with emphasis on Arrangement, Description and Diffusion of archives were debated, with focus on the elaboration of research instruments by ICA-AtoM (AtoM) in consonance with the national archive policy. The base of this study is consisted in raising the complete history of the institution and its document collection. The research has an applied nature, with a descriptive qualitative approach. Relative to the objectives, it is descriptive, and according to the technical procedures, constitutes a case study, grounded by the consult of the bibliography and the documents . This research allowed to identify and systematize the documentary fonds, establish a systematic arrangement for UFCSPA’s collection, as to create the research instruments guide and inventory to access and diffusion of the documental collections. As elaborated products, there are the guide (general) and the inventory (specific) of the collection of this university. Both instruments are fundamental to the information access. It is important to give continuity to the work through the elaboration of a catalogue and the online availability of other documental collections on the ICA-AtoM (AtoM) platform. This research could be applied to the IFES – Federal Higher Education Institutions, since they follow similar methodologies regarding the archival policies and have in common their core activities.